INNOVATIVE APPROACHES IN TEACHING PHILOLOGICAL SUBJECTS. PROBLEMS AND SOLUTIONS - Khakimova Dilshoda Oybek qizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The article sheds light on different worldwide innovative approaches offered by international linguistics and philologists. During the article, some recommendations for applying latest teaching methods to teaching atmosphere and discursive opinions of experts on approaches to philological subjects are included.